Expanding RNAi therapeutics to extrahepatic tissues with lipophilic conjugates - Brown, Kirk M.; Nair, Jayaprakash K.; Janas, Maja M.; Anglero-Rodriguez, Yesseinia I.; Dang, Lan T. H.; Peng, Haiyan; Theile, Christopher S.; Castellanos-Rizaldos, Elena; Brown, Christopher; Foster, Donald; Kurz, Jeffrey; Allen, Jeffrey; et al. (Nature biotechnology, 2022)
Therapeutics based on short interfering RNAs (siRNAs) delivered to hepatocytes have been approved, but new delivery solutions are needed to target additional organs. Here we show that conjugation of 2′- O -hexadecyl (C16) to siRNAs enables safe, potent and durable silencing in the central nervous system (CNS), eye and lung in rodents and non-human primates with broad cell type specificity. We show that intrathecally or intracerebroventricularly delivered C16-siRNAs were active across CNS regions and cell types, with sustained RNA interference (RNAi) activity for at least 3 months. Similarly, intravitreal administration to the eye or intranasal administration to the lung resulted in a potent and durable knockdown. The preclinical efficacy of an siRNA targeting the amyloid precursor protein was evaluated through intracerebroventricular dosing in a mouse model of Alzheimer’s disease, resulting in amelioration of physiological and behavioral deficits. Altogether, C16 conjugation of siRNAs has the potential for safe therapeutic silencing of target genes outside the liver with infrequent dosing. Lipophilic siRNA conjugates exert therapeutic activity in the mouse CNS.